The intersection between climate transition policies and geoeconomic fragmentation: A report of the International Relations Committee Network on climate change - Pierre-François Weber; Amandine Afota; Maria-Grazia Attinasi; Lukas Boeckelmann; Axel Brueggemann; Annabelle De Gaye; Alistair Dieppe; Violaine Faubert; Fabio Grieco; Julien Le Roux; Baptiste Meunier; Bogdan Munteanu; et al. (European Central Bank (ECB), 2025)
Two phenomena are increasingly reshaping the world economy. One is the growing and well-documented importance of climate transition policies that differ across countries. The other is the stark rise of geoeconomic fragmentation (GEF) concerns. While differences in climate transition policies are not new, they could amplify GEF, which is a new, growing risk. Conceptually, GEF is a policy-driven reversal of global economic integration, guided by strategic considerations such as national security, sovereignty, autonomy, or economic rivalry. It does not include reversals to global economic integration that are driven by autonomous change, such as shifts in technology, demographics or preferences, or policies motivated primarily by prudential or environmental concerns and labour or human rights. GEF propagates via all the channels through which countries engage with each other economically and politically to provide global public goods such as climate change mitigation. The steep rise in trade and investment restrictions points to coming headwinds which could be compounded by uncoordinated climate transition policies. Conversely, GEF could make transition policies more difficult as, together with their prerequisites - such as shared regulatory approaches, knowledge sharing and financial aid to less well-off countries - they hinge on effective cross-border coordination and collaboration. There is a considerable risk that GEF may hinder climate transition policies. The report is structured as follows. The first section sheds light on how climate policies may contribute to GEF. The second section analyses the extent to which GEF could hinder the green transition. The last section discusses gaps and avenues for further analytical and model-based work.
Keywords: F52; F64; H87; Q54; 330; Geoeconomic fragmentation; climate change; international public goods; international cooperation